Enhancing Student Learning Outcomes Through Quizizz-Supported Culturally Responsive Teaching in Problem-Based Learning - M Afifuddin Khotibul Umam; Elly Sukmanasa; Heldayanti Heldayanti; Indah Egi Pratiwi (Journal of General Education and Humanities, 2025)
Many students face academic engagement and achievement challenges due to the lack of culturally relevant instructional materials. This study examines the effectiveness of integrating Culturally Responsive Teaching (CRT) with Problem-Based Learning (PBL), supported by Quizizz, in improving student learning outcomes in Science and Social Studies (IPAS). Conducted as a Classroom Action Research (CAR) study using Stringer's model, the research involved two cycles with 28 fourth-grade students at SDN Empang 2 Bogor. Data collection methods included classroom observations, formative assessments, and student performance analysis. The findings indicate a significant improvement in student learning outcomes, with average scores increasing from 67 in Cycle 1 to 80 in Cycle 2. The proportion of students meeting the minimum competency threshold rose from 46% to 75%. A paired t-test confirmed that these improvements were statistically significant (p < 0.05, Cohen's d = 1.18), indicating a strong effect of the CRT-PBL model. Integrating culturally relevant content, problem-solving strategies, and gamified assessment through Quizizz enhanced student engagement, motivation, and conceptual understanding. This study highlights the potential of CRT-PBL combined with educational technology to foster active learning in diverse classrooms. Future research should explore its long-term impact and applicability across different subjects and educational settings.